Kefektivan Penggunaan Media Video Pembelajaran Untuk Meningkatkan Motivasi dan Hasil Belajar Kimia SMA - Gesa Salutri; Mohamad Agung Rokhimawan; Setia Rahmawan (UNIB Press, 2022)
The purpose of this research was to increase interest in learning chemistry using learning video media from reviewing articles. The research method used was a literature review. The results show a literature review conducted on 17 scientific journal articles with the use of instructional video media used in each article to increase motivation and learning outcomes. The summary of this review article on the use of instructional video media as a method of learning from the results of the article review is that there is an effect on students in student learning and also has no effect on students in student learning. Based on these results, we conclude that the developed learning media is suitable for use as learning media.